Project-Based Learning on STEAM-Based Student's Worksheet with Ecoprint Technique: Effects on Student Scientific Reasoning and Creativity - Irdalisa, Irdalisa; Paidi, Paidi; Panigrahi, Rashmi Ranjan; Hanum, Erlia (Jurnal Inovasi Pendidikan IPA, 2024)
The use of conventional worksheets will likely limit students' ability to explore themselves and their critical and analytical thinking, which can enhance their scientific reasoning and creativity. This situation demands the need for student worksheets linked to technology, art, and mathematics to adapt to the demands of the times. This study aims to determine the effect of project-based learning by analyzing student worksheets based on science, technology, engineering, arts, and mathematics (STEAM) using the eco-print technique on students' scientific reasoning and creativity. This research is a quasi-experimental study. The research sample is 160 students of a public senior high school in Jakarta, randomly selected and grouped into control and experimental groups, each consisting of 80 students. Data on scientific reasoning were collected using a test, while student creativity was measured with a questionnaire and observation sheet. The data obtained were analyzed using a one-way analysis of covariance at the significance level of 5%. The results show that the application of project-based learning on STEAM-based student worksheets using the eco-print technique significantly affects the students' achievement of scientific reasoning and creativity. The use of STEAM-based student worksheets with the eco-print technique serves as an innovative learning media to enhance the quality of education, as it can facilitate and increase active student engagement in collaborative projects that integrate various STEAM elements, thereby improving student competencies.